CLINICAL AND LABORATORY MANIFESTATIONS OF TUBERCULOUS SPONDYLITIS - Abduvakhob S. Baboev ,; Primkul H. Nazirov , (Central Asian Journal of Medicine, 2023)
The purpose of our study was to characterize the clinical and laboratory features of tuberculous spondylitis at the level of the general medical network. Materials and methods. Comprehensive examination of 110 patients with tuberculous spondylitis was conducted in the department of tuberculosis of bones and joints of the Republican Specialized Scientific and Practical Medical Center of Phthisiology and Pulmonology. Results. The study results showed decrease of blood hemoglobin levels and erythrocytes count in patients with tuberculous spondylitis. Blood acute-phase proteins were increased several times in patients with tuberculous spondylitis. Blood coagulation biochemical markers analyses showed an increased level of fibrinogen and D-dimers. Conclusion. Clinical and laboratory manifestations of tuberculous spondylitis in modern conditions are characterized by mild anemia, an increase in the blood of acute-phase proteins, fibrinogen, D dimers, reactive hepatitis and decrease of the blood fibrinolytic activity.